Laporan Kasus: Infeksi Isospora sp. Dan Toxocara cati Pada Kucing Lokal - Syafira Nurdillah Azis; Diana A Wuri; Julianty Almet (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Cats are a pet that is popular with many people. Cat health is an aspect that needs to be considered. Several diseases that are often found in cats are caused by worm parasites such as toxocariasis and protozoa such as coccidiosis. Diseases caused by these parasites show almost the same symptoms, namely diarrhea, decreased appetite, weakness, anorexia, and others which can be confirmed by fecal examination. Based on the results of laboratory examinations, the results showed that there were isospora sp oocysts. and Toxocara cati worm eggs. The treatment given was an antihelminthic, namely Pirantel Pamoate and antibiotics, namely Metronidazole. Prevention for Isospora sp infection. and T. cati need to pay attention to sanitation and cleanliness or cage management including a good environment as well as regular inspection and administration of worm medicine and regular health checks.